Equation (9.21) in the text gives the output of the Wheatstone bridge shown in Figure 3 as V_out = V-ex(R_1/R_1 + R_4 – R_2/R_2 + R_3) where the resistors may all be active strain gages. For this problem, assume that before any deformation (no strains) the bridge is balanced, with R_1 = R_2 = R_3 = R_4 = R. Figure 3. The Wheatstone bridge arrangement shown in Figure 9.23 of the text. Let R_1 be the only active gage. Under deformation its resistance changes to R_1 = R + Delta R, with Delta R

This content is for Premium members only.
sign up for premium and access unlimited solutions for a month at just 5$(not renewed automatically)




already a member please login